A presença dos aparelhos e dispositivos ópticos no Rio de Janeiro do século XIX - Silva, Maria Cristina Miranda da (2006)
The study investigates the presence of optical apparatus and optical devices in Brazil of century XIX, in special in the city of Rio de Janeiro, objectifying examining its users and diffusers, as well as the forms of comment and social contexts of the use the same ones The research is based on the studies of the early cinema, especially in Tom Gunning and Charles Musser, and in the workmanship of the historian of the art Jonathan Crary, the authors that help us, respectively, in the process of the recontextualizing of the use of optical devices and the dimensionality of the observer of modernity. The empirical work consists of the analysis of the orders of license to the city council of Rio de Janeiro for the exhibition of the devices in the period of 1830 the1890, and in the systematic study of the announcements published in newspapers in that period like Jornal do Commercio from 1850 to 1870. The organization and the categorization of the findings of the research prove that the popularization of the devices mentioned, over all in the street parties. Special emphasis was conferred on the arrival of the photograph in Brazil and the precocity with that the photographer Revert Henrique Klumb developed the Stereoscopy. Thematic that they had been the reference for the Brazilian visuality had been mapped and the Brazilian photographers who had developed this technique had been inventoried. From the announcements published in the Almanak Laemmert, between 1844 and 1889, we have done a survey of the establishments that imported and commercialized the apparatus and devices in the period in question. Taking into account all the information provided, the study questioned the presence of the optical apparatus and devices in the city of Rio de Janeiro in the 19th century, considering the particularities of them in the historical, economical and social context of the time